Haunted Ice, Fearful Sounds, and the Arctic Sublime: Exploring Nineteenth-Century Polar Gothic Space ... - Bowers, Katherine (Manchester University Press, 2017)
This article considers a unified polar Gothic as a way of examining texts set in Arctic and Antarctic space. Through analysis of Coleridge's' The Rime of the Ancient Mariner', Shelley's Frankenstein, and Poe's The Narrative of Arthur Gordon Pym of Nantucket , the author creates a framework for understanding polar Gothic, which includes liminal space, the supernatural, the Gothic sublime, ghosts and apparitions, and imperial Gothic anxieties about the degradation of 'civilisation'. Analysing Verne's scientific-adventure novel The Adventures of Captain Hatteras (1866) with this framework, the author contextualises the continued public interest in the lost Franklin expedition and reflects on nineteenth-century polar Gothic anxieties in the present day. Polar space creates an uncanny potential for seeing one's own self and examining what lies beneath the surface of one's own rational mind. ...